Analysis of Pregnant Women's Perceptions Regarding the Quality of Antenatal Care (ANC) Services at the Taratara Community Health Center, West Tomohon - Neni Anjelika Girsang; Nancy Silvia Bawiling; Deviana Pratiwi Munthe; Vera Diane Tombokan; Tika Bela Sari; Fredrik Alfrets Makadada (Akademi Keperawatan Yarsi Samarinda, 2026)
Antenatal Care (ANC) services are a crucial effort in improving maternal and fetal health and preventing pregnancy complications. Pregnant women's perceptions of ANC service quality play a role in their utilization of healthcare services during pregnancy. This study aims to analyze pregnant women's perceptions of ANC service quality at the Taratara Community Health Center (Puskesmas) based on the five dimensions of service quality (SERVQUAL): tangibles, reliability, responsiveness, assurance, and empathy. The study employs a qualitative method with a descriptive approach. Informants consisted of four pregnant women (primary informants) and one midwife (key informant), selected using purposive sampling. Data were collected through in-depth interviews, non-participant observation, and documentation. Data analysis was conducted using Braun and Clarke’s thematic analysis, while data validity was tested through source triangulation. The results indicate that, overall, pregnant women hold a positive perception of ANC service quality at the Taratara Community Health Center. The dimensions of tangibles, reliability, assurance, and empathy were perceived as meeting expectations, evidenced by adequate facilities, adherence to service procedures, healthcare worker competence, and a friendly, attentive attitude during service delivery. However, issues were identified regarding the responsiveness dimension, particularly concerning waiting time efficiency and the speed of staff response in certain situations. The study concludes that the dimensions of tangibles, reliability, assurance, and empathy should be maintained, whereas the responsiveness dimension requires improvement specifically regarding service speed and waiting time management to further optimize the quality of ANC services at the Taratara Community Health Center.